Guidelines and recommendations for radiologist staffing, education and training - Adrian P. Brady; Christian Loewe; Boris Brkljacic; Graciano Paulo; Martina Szucsich; Monika Hierath; on behalf of the European Society of Radiology (Insights into Imaging)
Abstract This article outlines the radiology-related staffing and education/training guidelines and recommendations developed by the European Commission-funded EU-REST (European Union Radiation, Education, Staffing & Training) project. The radiologist consortium partners propose the use of hour of machine/system/activity as the basic unit to calculate radiologist staffing needs. Education and training recommendations for radiologists include establishing 5 years as the standard duration of specialty training in radiology and establishing the ESR European Training Curriculum for Radiology as the European-wide standard. General recommendations for all professional groups include the maintenance of a central registry for each professional group and for relevant equipment, by each EU Member State, mandated CPD including techniques and knowledge relevant to each professional group, adoption vs adaptation of the project’s recommendations. Critical relevance statement The radiology-related staffing and education/training guidelines and recommendations developed by the EU-REST project propose a novel approach to calculate radiologist staffing numbers and provide recommendations regarding radiology education and training as well as general recommendations for all professional groups covered by the project. Key Points The pros and cons of taking population, workload, equipment or bed availability numbers as parameters to calculate radiology workforce are described. The reasons why these parameters are not suitable to calculate radiologist staffing needs are explained. The proposed use of hour of machine/system/activity as the basic unit to calculate radiologist staffing needs allows for establishing an adaptable and scalable guideline. Education and training recommendations for radiologists and non-profession-specific recommendations are summarised.